Some species of macro-gastropods in the coastal zone of Khanh Hoa province - Nghi, Bui Quang; Ngan, Nguyen Thi My; Phu, Nguyen Kha (Vietnam Journal of Marine Science and Technology, 2021)
From November 2013 to March 2014, 104 species were collected, belonging to 27 families, 58 genera of Gastropoda in coastal area of Khanh Hoa province. Some families have a large number of species such as Conidae - 15 species; Strombidae - 15 species; Cypraeidae - 10 species; Terebridae - 7 species and Muricidae - 6 species. Many species of economic value are used for food and fine arts. 11 species are listed in Vietnam Red Data Book. Besides, images and information of samples (collecting date, place of sample collection,...) are presented.